Family history of stroke and cardiovascular diseases in early-onset cryptogenic ischaemic stroke - Sihvo, Maximilian C.; Ylikotila, Pauli; Zedde, Marialuisa; Pascarella, Rosario; Sarkanen, Tomi; Jatuzis, Dalius; Ryliskiene, Kristina; Von Sarnowski, Bettina; Licenik, Radim; Ferdinand, Phillip; Korv, Janika; Korv, Liisa; et al. (Oxford University Press (OUP), 2026)
Background
Familial aggregation of stroke is well-documented, yet few studies have examined associations between stroke subtypes—particularly early-onset cryptogenic ischaemic stroke (eCIS)—and broader family history (FH) of cardiovascular disease. Such associations may provide insights into underlying etiologic mechanisms.
Methods
In this multicentre case–control study, we included eCIS patients aged 18–49 years and matched stroke-free controls. We analysed the association between FH of stroke, venous thromboembolism (VTE), coronary artery disease (CAD), aneurysms and eCIS using multivariable logistic regression, with a subgroup analysis stratifying patients by high-risk patent foramen ovale (HR-PFO).
Results
We enrolled 508 eCIS patients (182 [36%] with HR-PFO) and 520 controls. Compared with controls, patients more frequently reported FH of stroke among first-degree relatives (FDR) (20% vs. 14%, P = .01) and grandparents (47% vs. 39%, P = .01), FH of early-onset stroke among FDR (5% vs. 2%, P = .01) and FH of early-onset VTE among FDR (5% vs. 2%, P = .003). In adjusted analyses, eCIS was associated with FH of stroke among FDR (OR 1.50; 95% CI, 1.04–2.16) and grandparents (1.50; 1.12–1.99), with FH of early-onset stroke among FDR (2.36; 1.11–5.04); and with FH of early-onset VTE among FDR (3.45; 1.47–8.13). eCIS was also associated with FH of VTE among FDR (1.80, 1.09–2.98) in the presence of HR-PFO. FH of CAD or aneurysms was not associated with eCIS.
Conclusion
FH of stroke and VTE, particularly early-onset events and in the presence of HR-PFO, are associated with eCIS. These findings support familial predisposition and highlight prothrombotic mechanisms in eCIS.
Clinical trial registration
www.clinicaltrials.gov/study/NCT01934725